Natural infection of common cranes (Grus grus) with highly pathogenic avian influenza H5N1 in Serbia - Djurdjević, Biljana; Petrović, Tamaš; Gajdov, Vladimir; Vidanović, Dejan; Vučićević, Ivana; Samojlović, Milena; Pajić, Marko (Frontiers in Veterinary Science, 2024)
IntroductionThe late autumn epizootic of the highly pathogenic avian influenza virus (HPAIV) subtype H5N1 in Serbia in 2023 caused massive mortality in the migratory population of common cranes (Grus Grus). This is the first time HPAIV has been identified in the common crane in Serbia, leading to mass mortality of this bird species.MethodsTo understand the pathological impact of HPAIV in cranes, we evaluated the pathological changes in the tissues of common cranes. Additionally, we report genomic characterization of HPAI/H5N1. In total, 14 juvenile common crane carcasses were examined.ResultsInfected birds primarily exhibited neurologic signs, including ataxia and incoordination. Grossly, necrotizing pancreatitis was the most common finding, while microscopic lesions included necrosis, inflammation and hemorrhages in the lungs, spleen, brain, liver and kidneys. Based on RT-PCR, all birds were infected with the HPAI H5N1 virus, as viral RNA was detected in all 14 selected tissues. Genetic analysis revealed that our H5N1 isolate could be grouped with highly pathogenic avian influenza clade 2.3.4.4b, subgroup DA, and is very closely related to the H5N1 strains isolated from the common crane and turkey from Croatia, the common crane from Italy and the Ural owl from Slovakia.DiscussionOur findings showed that common cranes are highly susceptible to natural infection with the HPAI H5N1 virus of clade 2.3.4.4b and may serve as bio-sentinels for the presence of the HPAI virus in wildlife.